Leachable residual monomers from conventional and 3D printable poly(meth)acrylates - Münker, Tijmen J. A. G.; Van de Vijfeijken, Sophie E. C. M.; Kleverlaan, Cornelis J.; Becking, Alfred G. (Brazilian Dental Science, 2026)
Poly(meth)acrylates have been widely used in healthcare for dental prostheses, fixation of hip implants and skull reconstructions, and in cosmetics as manicure products. Unreacted monomers remain in the final product and could cause adverse reactions. The release pattern of these residual monomers are not known for all different compositions and processing methods of poly(meth)acrylates. Objective: This study aims to investigate the release patterns of residual monomers from different compositions and processing methods of poly(meth)acrylates. Material and Methods: Eluates from four representative poly(meth)acrylates (40 x 28 x 6.0 mm, height x outer radius x thickness; Vertex Self-Curing, Palacos R+G, NextDent C&B MFH, and DePuy CMW-3; n = 3) were examined by reversed-phase high-performance liquid chromatography (HPLC). The residual monomer leached into water at 37.0 ± 1.0°C and the concentration was measured at time points between one hour and 14 days. Results: The materials released concentrations of residual monomers between 22,75 ± 4,05 µg/g (NextDent C&B MFH) and 78,83 ± 7,67 µg/g (DePuy CMW-3) over 14 days. Palacos R+G released the lowest monomer concentration in the first hour (p<0.01) and potentially did not reach a plateau within the observed timeframe, but was comparable to Vertex Self-Curing after 14 days (42,54 ± 3,49 vs 46,26 ± 2,23 µg/g). NextDent C&B MFH, formed with methacrylate oligomers, released a significantly lower residual monomer concentration (p < 0.005) at 14 days compared to the other materials and did not follow pseudo-first order release kinetics in the observed period. Conclusion: Different compositions and processing methods for poly(meth)acrylates show different release patterns and quantities of residual monomers. It is therefore advisable to develop specific compositions of and processing methods for poly(meth)acrylates in the medical field that are optimized for their specific application. KEYWORDS Leaching; Medical device; Poly(methyl methacrylate); Release; Residual monomer